The Religious Formation of Graduate Ministry Students in an Online Wisdom Community - Michael Porterfield (Adult Education Research Conference, 2014)
This paper explores the formation of online wisdom communities and the experiences of doctoral students studying preaching within a hybrid theological preaching program. This study highlights how instructors can enhance the physicality in the online community experience, helping adult learners feel connected and thus have a high level of learning.